Nitric Oxide Overproduction in Tomato shr Mutant Shifts Metabolic Profiles and Suppresses Fruit Growth and Ripening - Bodanapu, Reddaiah; Gupta, Suresh K.; Basha, Pinjari O.; Sakthivel, Kannabiran; Sadhana; Sreelakshmi, Yellamaraju; Sharma, Rameshwar (Frontiers in Plant Science, 2016)
Nitric oxide (NO) plays a pivotal role in growth and disease resistance in plants. It also acts as a secondary messenger in signaling pathways for several plant hormones. Despite its clear role in regulating plant development, its role in fruit development is not known. In an earlier study, we described a short root (shr) mutant of tomato, whose phenotype results from hyperaccumulation of NO. The molecular mapping localized shr locus in 2.5 Mb region of chromosome 9. The shr mutant showed sluggish growth, with smaller leaves, flowers and was less fertile than wild type. The shr mutant also showed reduced fruit size and slower ripening of the fruits post-mature green stage to the red ripe stage. Comparison of the metabolite profiles of shr fruits with wild-type fruits during ripening revealed a significant shift in the patterns. In shr fruits intermediates of the tricarboxylic acid (TCA) cycle were differentially regulated than WT indicating NO affected the regulation of TCA cycle. The accumulation of several amino acids, particularly tyrosine, was higher, whereas most fatty acids were downregulated in shr fruits. Among the plant hormones at one or more stages of ripening, ethylene, Indole-3-acetic acid and Indole-3-butyric acid increased in shr, whereas abscisic acid declined. Our analyses indicate that the retardation of fruit growth and ripening in shr mutant likely results from the influence of NO on central carbon metabolism and endogenous phytohormones levels.